Transformation of the Community of Believers in the Almighty God: A Sociological Analysis - Pak Wii; Sota Yamamoto; Sakura Suzuki (Journal of Noesantara Islamic Studies, 2025)
The community of believers in the One Almighty God in Indonesia has undergone significant transformation, especially after the legal recognition through the Constitutional Court ruling in 2017. This transformation not only covers social, cultural, and economic aspects, but also involves changes in the structure of collective identity and negotiation of their position amidst the dominance of the majority religion. This article analyzes the transformation process through a sociological approach, referring to the theories of functionalism, social conflict, and symbolic interaction. The main focus includes identity dynamics, social interaction patterns, integration challenges, and the role of belief organizations in preserving local traditions while adapting to modern norms. This analysis also highlights how legal recognition has opened up space for believers to strengthen their position in society, although challenges such as social stigma and marginalization are still faced. This transformation, ultimately, reflects efforts to create social harmony and maintain diversity in a pluralistic Indonesian society.